Concentrated Control, Analyst Following, and Valuation: Do Analysts Matter Most When Investors Are Protected Least? - Lang, Mark H.; Lins, Karl V.; Miller, Darius P. (Journal of Accounting Research, 2004)
This paper uses a sample of more than 2,500 firms from 27 countries to investigate the relation among ownership structure, analyst following, investor protection, and valuation. We find that analysts are less likely to follow firms with potential incentives to withhold or manipulate information, such as when the family/management group is the largest control rights blockholder. Furthermore, this relation is stronger for firms from low‐shareholder‐protection countries. Using valuation regressions that take into account potential endogeneity between analyst following and firm value, we find a positive valuation effect when analysts cover firms that have both potentially poor internal governance and weak country‐level external governance. Overall, our findings suggest that corporate governance plays an important role in analysts' willingness to follow firms and that increased analyst following is associated with higher valuations, particularly for firms likely to face governance problems.